Efficacy of Liraglutide in Obesity in Children and Adolescents: Systematic Review and Meta-Analysis of Randomized Controlled Trials - Cornejo-Estrada, Alejandra (2023)
In the past few decades, childhood obesity has become a significant global health issue, impacting around 107.7 million children and adolescents globally. There is currently minimal usage of pharmacological therapies for childhood obesity in the pediatric population. This research assessed the efficacy of liraglutide in treating childhood and adolescent obesity. Until 20 October 2022, a systematic literature review was done utilizing PubMed, Scopus, Web of Science, and Embase databases. The search phrases “liraglutide”, “pediatric obesity”, “children”, and “adolescents” were utilized. Using the search method, a total of 185 articles were found. Three studies demonstrating liraglutide’s effectiveness in treating child and adolescent obesity were included. The selected research was done in the United States. As an intervention, liraglutide was administered to 296 participants at a maximal dosage of 3.0 mg. All examined trials were in phase 3. This comprehensive analysis revealed no clinically significant differences between liraglutide and body weight (kg; MD −2.62; 95%CI −6.35 to 1.12; p = 0.17) and body mass index (kg/m2; MD −0.80; 95%CI −2.33 to 0.73, p = 0.31). There was no evidence that liraglutide increased hypoglycemia episodes (RR 1.08; 95%CI 0.37 to 3.15; p = 0.79), or side consequences. However, it was shown that the medicine might help reduce BMI and weight combined with a healthy diet and regular exercise. A lifestyle change may have favorable consequences that will be assessed in the future for adjunctive therapy. PROSPERO database (CRD42022347472)